Bio-based resin environment-friendly gum dipping solution, preparation method thereof and gum dipping method of fiber skeleton material

By using bio-based resin environmentally friendly impregnant solution prepared by bio-based materials such as guaiac-liquid-p-hydroxyphenyllignin, glyoxal and tannin, the problem of poor adhesion performance between fiber and rubber is solved, performance comparable to that of RFL impregnation system is achieved, and the risk of pollution in the environment and human body is reduced.

CN119913754APending Publication Date: 2025-05-02BEIJING UNIV OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311417373.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The interface bonding performance between existing fibers and rubber is poor, especially fibers with higher modulus, which are difficult to reach the same level as RFL glue-impregnation systems, and the toxicity and contamination of resorcinol and formaldehyde in traditional glue-impregnation systems are high.

Method used

A bio-based resin environmentally friendly impregnant solution was prepared using bio-based materials such as guaiac-liquid-p-hydroxyphenyllignin, glyoxal and tannin. The pH value is adjusted by ammonia water, combined with styrene butadiene latex to form a resin network to improve the interface adhesion between fiber and rubber.

Benefits of technology

The performance of this bio-based resin environmentally friendly impregnation liquid is comparable to that of the RFL impregnation system, and can significantly improve the interface adhesion between fiber and rubber matrix, reduce environmental pollution and human toxicity, and conform to the concept of low-carbon and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004519971990000131
    Figure BDA0004519971990000131
  • Figure BDA0004519971990000141
    Figure BDA0004519971990000141
  • Figure BDA0004519971990000142
    Figure BDA0004519971990000142
Patent Text Reader

Abstract

The invention discloses a bio-based resin environment-friendly gum dipping solution, a preparation method thereof and a gum dipping method of a fiber skeleton material, and belongs to the technical field of fiber gum dipping solutions. According to the invention, guaiacol-syringyl-p-hydroxyphenyl lignin, glyoxal and tannic acid are adopted to prepare the bio-based resin environment-friendly gum dipping solution. In the bio-based resin environment-friendly gum dipping solution disclosed by the invention, the glyoxalated guaiacol-syringyl-p-hydroxyphenyl lignin and the tannic acid generate resin with a cross-linked network structure; the resin contains a large number of hydroxyl groups, can be well bonded with the fiber surface, and can be mutually interspersed with two phases of latex, so that the interface bonding between the fiber and a rubber matrix is improved. After the fiber framework material is subjected to impregnation treatment by adopting the impregnation liquid, the fiber framework material and rubber have relatively high interface adhesive force, and the effect of the impregnation liquid can reach or be superior to the effect of a traditional RFL impregnation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fiber dipping solution, and further to a bio-based resin environmentally friendly dipping solution and a preparation method thereof, and a dipping method for a fiber skeleton material. Background Art

[0002] For rubber products such as tires and conveyor belts, the skeleton material bears most of the load during use and maintains the shape stability. Synthetic fibers such as polyester, nylon, aramid, and polyimide are gradually replacing steel cords as skeleton materials due to their advantages such as high specific strength and specific modulus. The interfacial adhesion between the skeleton material and rubber greatly affects the performance and life of the composite material. The surface of synthetic fibers is relatively smooth and mostly chemically inert. Therefore, the interfacial adhesion between synthetic fibers and rubber is poor after being directly compounded, and pretreatment is often required to improve the interfacial adhesion.

[0003] At present, the most widely used pretreatment method is the dipping method, in which the fiber is impregnated with a dipping solution. As for the dipping solution, the most ideal and commonly used dipping system is the resorcinol-formaldehyde-latex (RFL) dipping system; however, the resorcinol and formaldehyde used in the RFL dipping system are highly toxic and polluting. As people pay more attention to health and environmental protection, it is particularly important to use an environmentally friendly dipping system to replace the RFL dipping system. In recent years, there have been many reports on environmentally friendly alternatives to resorcinol formaldehyde at home and abroad.

[0004] CN105051284A discloses a dipping solution composed of acrylic resin, epoxy resin, blocked isobutyric acid, styrene butadiene latex and styrene butadiene pyridine latex. When applied to fabrics, its peel strength can reach the same level as RFL. WO2014175844A2 discloses a dipping solution composed of latex, epoxy compound, and polyether polyamine. When applied to aramid cord, it has a good bonding effect. CN112832030A discloses a dipping solution composed of mixed blocked isocyanate, polyol, polyamine and rubber latex. After impregnating aramid fiber and aramid nylon blended fiber, its H extraction force can reach the same level as RFL. CN112176729A discloses a dipping solution composed of epoxy resin, maleic anhydride grafted polyolefin, imidazole or amine curing agent, nanofiller and latex. When applied to aramid fiber and nylon fiber, it has a significant improvement in interface bonding. Although these dipping systems can improve interfacial bonding to a certain extent, it is difficult to achieve the same level of RFL, especially for fibers with higher modulus and poorer bonding properties, the interfacial bonding effect is even worse. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention uses guaiacyl-syringyl-p-hydroxyphenyl lignin, tannic acid and other bio-based materials as raw materials to prepare a fiber impregnation solution, which can reduce environmental pollution compared with other environmentally friendly systems. At the same time, the guaiacyl-syringyl-p-hydroxyphenyl lignin, a by-product produced by corn cob sugar extraction and papermaking, can be reused, which is more in line with the concept of low-carbon and environmental protection.

[0006] One of the purposes of the present invention is to provide an environmentally friendly bio-based resin dipping solution.

[0007] The bio-based resin environmentally friendly dipping solution is prepared by mixing raw materials including the following components and adjusting the pH value with ammonia water; the components and their weight parts are as follows:

[0008] Deionized water 100 parts by weight;

[0009] 100-140 parts by weight of styrene-butadiene latex, preferably 100-120 parts by weight;

[0010] Glyoxal 0.4-1.2 parts by weight, preferably 0.5-1 parts by weight;

[0011] 4-6 parts by weight, preferably 5-6 parts by weight, of tannic acid;

[0012] 2-4 parts by weight, preferably 2-3 parts by weight, of guaiacyl-syringyl-p-hydroxyphenyl lignin;

[0013] Sodium hydroxide 0.5-1 part by weight, preferably 0.6-0.8 part by weight.

[0014] The bio-based resin environmentally friendly dipping solution disclosed in the present invention has bio-based polyguaiacyl-syringyl-p-hydroxyphenylpropane, tannic acid, and glyoxal as main resin components, and its toxicity is significantly reduced compared to resorcinol and formaldehyde, and its performance is equivalent to or even better than that of the RFL dipping system, and it is an environmentally friendly dipping system that can replace the RFL dipping system. In addition, the bio-based polyphenylpropane is polyguaiacyl-syringyl-p-hydroxyphenylpropane, and its source can be a by-product of corn cob sugar extraction, papermaking and other industries; compared with other environmentally friendly systems, it can reduce environmental pollution, is more in line with the concept of low-carbon environmental protection, and is a sustainable bio-based system.

[0015] The styrene-butadiene latex described in the present invention cannot be replaced by other latexes. The reason is that compared with other latexes, the styrene-butadiene latex has a higher modulus and can better transfer stress between low-modulus rubber and high-modulus fiber; if other latexes are used to replace the styrene-butadiene latex, the interfacial adhesion performance will decrease. Therefore, the bio-based resin environmentally friendly dipping solution of the present invention uses styrene-butadiene latex instead of other latexes.

[0016] In the present invention, the sodium hydroxide cannot be replaced by potassium hydroxide because potassium hydroxide is easier to ionize than sodium hydroxide. If potassium hydroxide is used to replace sodium hydroxide, the alkalinity will be stronger at the same concentration, making the latex components in the dipping solution system prone to flocculation and instability.

[0017] In the present invention, if the pH value of the bio-based resin environmentally friendly dipping solution is too high or too low, it will cause flocculation of the styrene-butadiene latex and affect the stability of the dipping solution. Therefore, the present invention preferably adjusts the pH value of the bio-based resin environmentally friendly dipping solution to 9-11. In some embodiments disclosed in the present invention, the pH value of the bio-based resin environmentally friendly dipping solution is 10.

[0018] The present invention uses ammonia water to adjust the pH more gently and is not easy to cause latex flocculation. Based on 100 parts by weight of deionized water, it usually takes 1-2 parts by weight of ammonia water with a mass concentration of 28% to adjust the pH to 9-11, and in more cases, 1-1.5 parts by weight. In some embodiments of the present invention, 1.3 parts by weight of ammonia water with a mass concentration of 28% is required to adjust the pH of the bio-based resin environmentally friendly dipping solution to 9-11.

[0019] In the present invention, if the solid content of styrene butadiene latex is too high, the resin content in the dipping layer will be reduced, so that the modulus of the dipping layer will decrease, affecting stress transfer; at the same time, the dipping solution will be more viscous, so that the dipping layer is too thick, and the thickness of the dipping layer is too thick, which will affect the migration of sulfur in the rubber matrix and affect the co-vulcanization of styrene butadiene rubber and the rubber matrix in the dipping layer, thereby affecting the transfer of stress and causing the interface adhesion performance to decrease. If the solid content of styrene butadiene latex is too low, the content of styrene butadiene rubber in the dipping layer will be too low, thereby reducing the co-vulcanization degree of the dipping layer and the rubber matrix, and also affecting stress transfer and reducing interface adhesion performance. Therefore, the present invention preferably limits the solid content of the styrene butadiene latex to 30-50%.

[0020] The second object of the present invention is to provide a method for preparing the above-mentioned bio-based resin environmentally friendly dipping solution provided by the first object of the invention.

[0021] The preparation method comprises: mixing sodium hydroxide and deionized water, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin to dissolve it, adding glyoxal and stirring, adding tannic acid to dissolve it, adding ammonia water to adjust the pH value, adding styrene-butadiene latex and stirring to obtain the environmentally friendly bio-based resin dipping solution.

[0022] Wherein, the glyoxal is preferably added in the form of a glyoxal aqueous solution. For example, a glyoxal aqueous solution with a mass concentration of 40% is used. Based on 100 parts by weight of deionized water, the amount of the glyoxal aqueous solution with a mass concentration of 40% is 1.0-3.0 parts by weight, preferably 1.2-2.4 parts by weight.

[0023] The purpose of stirring in "adding glyoxal and stirring" is to mix evenly, and stirring is usually required for more than 12 hours after adding glyoxal. The purpose of stirring in "adding butadiene styrene latex and stirring" is to ensure that the components are evenly distributed, and stirring is usually required for more than 3 hours after adding butadiene styrene latex. "Dissolving it" can usually be achieved by stirring. For example, after adding tannic acid, it can be stirred for about 15-20 minutes to dissolve it.

[0024] The third object of the present invention is to provide a method for impregnating a fiber skeleton material using the bio-based resin environmentally friendly impregnation solution provided in one of the objects of the invention.

[0025] The dipping method comprises: dipping the fiber skeleton material in a first bath, drying and heat treating, and then dipping in a second bath using the bio-based resin environmentally friendly dipping solution. In some embodiments of the present invention: dipping in an activation solution bath for 2 seconds, drying at 150°C for 1.5 minutes, heat treating at 230°C for 1.5 minutes, and then dipping in a second bath.

[0026] The first bath immersion is carried out using an activation solution comprising deionized water, an aqueous epoxy resin and a blocked isocyanate. Specifically, the first bath immersion is carried out using an activation solution consisting of deionized water, an aqueous epoxy resin and a blocked isocyanate. In some embodiments of the present invention: an activation solution consisting of 91.7 parts by weight of deionized water, 1.3 parts by weight of an aqueous epoxy resin and 7.0 parts by weight of a blocked isocyanate is used.

[0027] The immersion time of the second bath immersion is usually determined by the speed of the dipping process, and the change of the immersion time has little effect on the performance of the product, so it is not limited. In some embodiments of the present invention, the immersion time of the second bath immersion is 2s.

[0028] The dipping method further comprises: after dipping in the second bath, drying at 180-190°C for 1-2 minutes, and then heat treating at 230-250°C for 1-2 minutes; preferably, the heat treatment temperature is 240-250°C.

[0029] The fiber skeleton material is one or more of polyimide fiber, nylon 6 fiber, nylon 66 fiber, polyester PET fiber, polyester PEN fiber and aramid fiber. The fiber can be in the form of monofilament, cord, curtain or canvas.

[0030] According to some embodiments disclosed in the present invention, a fiber skeleton material adopts the bio-based resin environmentally friendly dipping solution provided in one of the invention purposes. The fiber skeleton material is immersed in the activation solution in a bath for 2 seconds, dried at 150°C for 1.5 minutes, and heat-treated at 230°C for 1.5 minutes, and then immersed in a second bath. After the fiber skeleton material is immersed in the second bath for 2 seconds, it is dried at 180-190°C for 1-2 minutes and heat-treated at 230-250°C for 1-2 minutes.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The bio-based resin environmentally friendly dipping solution disclosed in the present invention utilizes three bio-based raw materials, guaiacyl-syringyl-p-hydroxyphenyl lignin, glyoxal and tannic acid, to replace the resin network generated by traditional resorcinol formaldehyde. The generated resin network is similar to resorcinol formaldehyde resin, contains a large number of hydroxyl groups, and has good adhesion performance with the fiber surface. At the same time, the resin and latex can interpenetrate each other, and the latex part can be co-vulcanized with the rubber matrix, and the resin can be bonded to the fiber, thereby transmitting stress between the fiber and the rubber matrix, and significantly improving the interface adhesion between the fiber and the rubber matrix.

[0033] After the fiber skeleton material is impregnated with the environmentally friendly bio-based resin impregnation liquid disclosed in the present invention, the post-H extraction force can reach the level of the traditional RFL impregnation system. At the same time, the preparation process of the impregnation liquid of the impregnation system is simpler. Compared with the traditional RFL impregnation system, the impregnation process does not need to be significantly changed, which is convenient for direct replacement.

[0034] The guaiacyl-syringyl-p-hydroxyphenyl lignin used in the bio-based resin environmentally friendly dipping solution disclosed in the present invention is a byproduct of papermaking or corn cob sugar extraction, and tannic acid is extracted from plant resources such as gallnut. Glyoxal can also be prepared from bio-based raw materials such as ethanol, sugar, and ethanol, and glyoxal is a non-volatile aldehyde, and its toxicity and pollution are significantly lower than the RFL dipping system. By using the above bio-based raw materials as bio-based resins to replace resorcinol and formaldehyde with higher toxicity and pollution, the pollution to the human body and the environment during the preparation and use of the dipping solution can be significantly reduced, and carbon emissions can be effectively reduced, which is in line with the concept of environmental protection and sustainable development. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0036] The reagents used in the examples and comparative examples are all commercially available products. The guaiacyl-syringyl-p-hydroxyphenyl lignin used is LIG-II lignin from Shandong Longli Biotechnology Co., Ltd.

[0037] Example 1

[0038] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0039] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0040] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% (mass concentration, the same below) glyoxal aqueous solution, 1.3 weight parts of 28% (mass concentration, the same below) ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0041] The preparation method of the second-bath dipping solution is as follows: according to the above weight parts, sodium hydroxide and deionized water are added into a reaction container to prepare an alkaline solution, then guaiacyl-syringyl-p-hydroxyphenyl lignin is added into the alkaline solution and stirred to dissolve, then a 40% glyoxal aqueous solution is added, and after stirring at room temperature for 12 hours, tannic acid is added and stirred to dissolve, then ammonia water is added, and finally latex is added, and stirred at room temperature for 3 hours to obtain a bio-based resin environmentally friendly dipping solution with a pH of 10.

[0042] Example 2

[0043] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0044] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0045] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 1.0 weight part of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0046] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0047] Example 3

[0048] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0049] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0050] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 3.0 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0051] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0052] Example 4

[0053] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0054] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0055] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 4 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0056] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0057] Example 5

[0058] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0059] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0060] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 6 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0061] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0062] Example 6

[0063] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0064] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0065] The components of the second bath dipping solution and their weight parts are: 2 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0066] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0067] Example 7

[0068] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0069] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0070] The components of the second bath dipping solution and their weight parts are: 4 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0071] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0072] Example 8

[0073] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 240°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0074] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0075] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0076] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0077] Example 9

[0078] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0079] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0080] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of dealkalized guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 100 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0081] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0082] Example 10

[0083] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0084] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0085] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 140 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0086] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0087] Embodiment 11

[0088] The fiber skeleton material is immersed in the activation liquid for 2 seconds, dried at 150℃ for 1.5 minutes, heat treated at 230℃ for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190℃ for 1.5 minutes, and heat treated at 250℃ for 1.5 minutes. The fiber skeleton material uses aramid fiber cord.

[0089] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0090] The components of the second bath dipping solution and their weight parts are: 2.5 weight parts of dealkalized guaiacyl-syringyl-p-hydroxyphenyl lignin, 5.46 weight parts of tannic acid, 0.68 weight parts of sodium hydroxide, 2.4 weight parts of 40% glyoxal aqueous solution, 1.3 weight parts of 28% ammonia water, 120 weight parts of styrene-butadiene latex, and 100 weight parts of deionized water.

[0091] The preparation method comprises the following steps: adding sodium hydroxide and deionized water into a reaction container according to the above weight parts to prepare an alkaline solution, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin into the alkaline solution and stirring to dissolve it, then adding glyoxal solution, stirring and placing at room temperature for 12 hours, adding tannic acid and stirring to dissolve it, then adding ammonia water to adjust the pH value, and finally adding latex, stirring at room temperature for 3 hours to obtain an environmentally friendly bio-based resin dipping solution with a pH of 10.

[0092] Comparative Example 1

[0093] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0094] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0095] The second bath uses the traditional RFL dipping system to impregnate the fiber cord.

[0096] Comparative Example 2

[0097] The fiber skeleton material is polyimide fiber cord, which is treated in one bath. The fiber skeleton material is immersed in the activation solution in one bath for 2 seconds, dried at 150°C for 1.5 minutes, and heat treated at 230°C for 1.5 minutes.

[0098] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0099] Comparative Example 3

[0100] The fiber skeleton material is immersed in the activation solution for 2 seconds, dried at 150°C for 1.5 minutes, heat treated at 230°C for 1.5 minutes, and then immersed in the second bath. The fiber skeleton material is immersed in the second bath for 2 seconds, dried at 190°C for 1.5 minutes, and heat treated at 250°C for 1.5 minutes. The fiber skeleton material uses polyimide fiber cord.

[0101] The components and weight proportions of the one-bath activation solution are as follows: 91.7 weight proportions of deionized water, 1.3 weight proportions of waterborne epoxy resin, and 7.0 weight proportions of blocked isocyanate.

[0102] The components of the second-bath dipping solution and their weight portions are: 2.5 weight portions of alkali lignin, 5.46 weight portions of tannic acid, 0.68 weight portions of sodium hydroxide, 2.4 weight portions of 40% (mass concentration, the same below) glyoxal aqueous solution, 1.3 weight portions of 28% (mass concentration, the same below) ammonia water, 120 weight portions of styrene-butadiene latex, and 100 weight portions of deionized water.

[0103] The preparation method of the two-bath dipping solution is as follows: according to the above-mentioned weight parts, sodium hydroxide and deionized water are added into a reaction container to prepare an alkaline solution, then alkaline lignin is added into the alkaline solution and stirred to dissolve, then a 40% glyoxal aqueous solution is added, and after stirring at room temperature for 12 hours, tannic acid is added and stirred to dissolve, then ammonia water is added, and finally latex is added, and stirred at room temperature for 3 hours to obtain a bio-based resin environmentally friendly dipping solution with a pH of 10.

[0104] The fiber skeleton materials treated in the examples and comparative examples were subjected to H extraction force test. The preparation and test method of H extraction specimens were carried out in accordance with the standard GB / T 2942-2009, with a vulcanization temperature of 150°C and a vulcanization time of 20 minutes; the rubber compound formula used is shown in Table 1, and the test results are shown in Table 2.

[0105] Table 1

[0106]

[0107]

[0108] Table 2

[0109]

[0110] The second bath dipping solution of Comparative Example 3 contains alkali lignin, and the second bath dipping solution of Example 1 contains guaiacyl-syringyl-p-hydroxyphenyl lignin; the only difference between Example 1 and Comparative Example 3 is that the lignin used in the second bath dipping solution is different. It can be seen from the data in Table 2 that the H extraction force of the fiber skeleton material treated in Example 1 (the H extraction force is 179.6N) is increased by 19% relative to the H extraction force of the fiber skeleton material treated in Comparative Example 3 (the H extraction force is 150.9N). The H extraction force of the fiber skeleton material treated in Examples 2-11 (the H extraction force is 159.3-186.5N) is higher than the H extraction force of the fiber skeleton material treated in Comparative Example 3. It can be seen that the dipping solution formed by compounding guaiacyl-syringyl-p-hydroxyphenyl lignin with other components has better performance than other lignins.

[0111] It can be seen from the data in Table 2 that the amount of guaiacyl-syringyl-p-hydroxyphenyl lignin, tannic acid, glyoxal, butadiene pyridine latex and the change in heat treatment temperature in the environmentally friendly bio-based resin dipping solution prepared in the embodiment will affect the H extraction force of the environmentally friendly bio-based resin dipping solution. In particular, the changes in the amount of the three components of guaiacyl-syringyl-p-hydroxyphenyl lignin, tannic acid, and glyoxal have a more obvious effect on the H extraction force of the environmentally friendly bio-based resin dipping solution. Compared with the RFL dipping system of Comparative Example 1, the bio-based environmentally friendly dipping solution prepared in the embodiment can achieve a considerable H extraction force level. Even, the H extraction force level of the bio-based environmentally friendly dipping solution prepared in Example 1 is higher than the H extraction force level of the RFL dipping system of Comparative Example 1. The data in Table 2 prove that the bio-based environmentally friendly dipping solution provided by the present invention has excellent performance.

Claims

1. A bio-based resin environmentally friendly dipping solution, characterized in that: The bio-based resin environmentally friendly dipping solution is prepared by mixing raw materials including the following components and adjusting the pH to alkaline using ammonia water; The components and their weight parts are as follows: Deionized water 100 parts by weight; 100-140 parts by weight of styrene-butadiene latex, preferably 100-120 parts by weight; Glyoxal 0.4-1.2 parts by weight, preferably 0.5-1 parts by weight; 4-6 parts by weight, preferably 5-6 parts by weight, of tannic acid; 2-4 parts by weight, preferably 2-3 parts by weight, of guaiacyl-syringyl-p-hydroxyphenyl lignin; Sodium hydroxide 0.5-1 part by weight, preferably 0.6-0.8 part by weight.

2. The environmentally friendly bio-based resin dipping solution according to claim 1, characterized in that: The solid content of the styrene-butadiene latex is 30-50%.

3. The environmentally friendly bio-based resin dipping solution according to claim 1, characterized in that: Adjust pH to 9-11.

4. A method for preparing the environmentally friendly bio-based resin dipping solution as claimed in claim 1, 2 or 3, characterized in that: The preparation method comprises: mixing sodium hydroxide and deionized water, then adding guaiacyl-syringyl-p-hydroxyphenyl lignin to dissolve it, adding glyoxal and stirring, adding tannic acid to dissolve it, adding ammonia water to adjust the pH value, adding styrene-butadiene latex and stirring to obtain the environmentally friendly bio-based resin dipping solution.

5. The preparation method according to claim 4, characterized in that: The glyoxal is added in the form of a glyoxal aqueous solution.

6. The preparation method according to claim 4, characterized in that: Add glyoxal and stir for more than 12 hours; or / and, add styrene-butadiene latex and stir for more than 3 hours.

7. A method for impregnating a fiber skeleton material, characterized in that: The dipping method comprises: the fiber skeleton material is dipped in a first bath, and after drying and heat treatment, it is dipped in a second bath using the bio-based resin environmentally friendly dipping solution as claimed in claim 1, 2 or 3.

8. The dipping method according to claim 7, characterized in that: The first bath immersion is carried out using an activation solution containing deionized water, water-based epoxy resin and blocked isocyanate.

9. The dipping method according to claim 7, characterized in that: The dipping method further comprises: after dipping in the second bath, drying at 180-190°C for 1-2 minutes, and then heat treating at 230-250°C for 1-2 minutes; preferably, the heat treatment temperature is 240-250°C.

10. The dipping method according to claim 7, characterized in that: The fiber skeleton material is one or more of polyimide fiber, nylon 6 fiber, nylon 66 fiber, polyester PET fiber, polyester PEN fiber and aramid fiber.

Citation Information

Patent Citations

  • Lignin for dipping fibers and preparation method of lignin and fiber dipping method by lignin

    CN104844807A

  • Fiber skeleton material impregnation liquid and preparation method thereof, and impregnation method

    CN110511459A

  • Lignin derivative, lignin second derivative, lignin resin composition, prepreg, and composite structure

    JP2012177035A

  • Lignin resin composition, prepreg, and composite structure

    JP2013035970A

  • Lignin derivative for rubber reinforcement, lignin resin composition and rubber composition

    JP2016060749A